123k views
5 votes
2(5m^4n^-1)^3 simplify show work please

User Victorx
by
5.1k points

1 Answer

3 votes

Answer:


\large\boxed{2(5m^4n^(-1))^3=250m^(12)n^(-3)=(250m^(12))/(n^3)}

Explanation:


\text{Use}\\\\(ab)^n=a^nb^n\\\\(a^n)^m=a^(nm)\\\\a^(-n)=(1)/(a^n)\\-------------------\\\\2(5m^4n^(-1))^3=2(5)^3(m^4)^3(n^(-1))^3=2(125)m^(3\cdot4)n^(-1\cdot3)=250m^(12)n^(-3)=(250m^(12))/(n^3)

User Gavin Thornton
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.